2016
DOI: 10.1159/000453104
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gyrification in Carnivores

Abstract: The order Carnivora is a large and highly diverse mammalian group with a long and well-documented evolutionary history. Nevertheless, our knowledge on the degree of cortical folding (or degree of gyrification) is limited to just a few species. Here we investigate the degree of cortical folding in 64 contemporary and 37 fossil carnivore species. We do so by measuring the length of gyri impressions on endocranial casts. We use this approach because we have found that there is a very good correlation between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…To date few descriptions of the anatomy of the brains of wild canids are available (limited to endocast morphology, e.g., Radinsky, 1969Radinsky, , 1973Lyras & Van der Geer, 2003;Lyras, Giannakopoulou, Kouvari, & Papadopoulos, 2016), which is in direct contrast to many comprehensive studies of the brain of the domestic dog (e.g., Beitz & Fletcher, 1993;Fox, 1971;Palazzi, 2011;Singer, 1962). Here we have provided a comprehensive description of the brain of the African wild dog, which, due to its specialized social behavioral repertoire (Creel & Creel, 1995;Gusset et al, 2006;Robbins & McCreery, 2000;Skinner & Chimimba, 2005;Thomas et al, 2006;van den Berghe et al, 2012;Walker et al, 2017) and phylogenetic position within the canids (Bardeleben et al, 2005;Lindblad-Toh et al, 2005), is of interest in understanding the derived and shared neural features of the various members of the canid lineage, including the domestic dog.…”
Section: Discussionmentioning
confidence: 99%
“…To date few descriptions of the anatomy of the brains of wild canids are available (limited to endocast morphology, e.g., Radinsky, 1969Radinsky, , 1973Lyras & Van der Geer, 2003;Lyras, Giannakopoulou, Kouvari, & Papadopoulos, 2016), which is in direct contrast to many comprehensive studies of the brain of the domestic dog (e.g., Beitz & Fletcher, 1993;Fox, 1971;Palazzi, 2011;Singer, 1962). Here we have provided a comprehensive description of the brain of the African wild dog, which, due to its specialized social behavioral repertoire (Creel & Creel, 1995;Gusset et al, 2006;Robbins & McCreery, 2000;Skinner & Chimimba, 2005;Thomas et al, 2006;van den Berghe et al, 2012;Walker et al, 2017) and phylogenetic position within the canids (Bardeleben et al, 2005;Lindblad-Toh et al, 2005), is of interest in understanding the derived and shared neural features of the various members of the canid lineage, including the domestic dog.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is less convoluted than in Pinnipedia: Zalophus californianus (Montie et al, 2009), northern fur seal ( Callorhinus ursinus ) and Steller sea lion ( Eumetopias jubatus ) (based on specimens available in CMBC). Gyrification studies showed the polar bear ( Ursus maritimus ) having a considerably more convoluted brain surface than other sampled Carnivora species, surpassed only by two Pinnipedia species (Lyras et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(Frey et al, 2011;Grohé et al, 2012;Mahboubi et al, 2014). A study by Lyras et al (2016) suggested that aquatic and semi-aquatic carnivorans as a rule have more gyrencephalic brains than terrestrial ones, but this is not the case with A. macrognathus. The homology between the functional regions of the cortex in hyaenodonts and carnivorans is currently not sufficiently established to speculate about more specific sensory adaptations such as those seen in the otter (Radinsky, 1968).…”
Section: Comparison Of Hyaenodont Endocastsmentioning
confidence: 99%